USAGE OF VECTOR PARAMETRIC OPTIMIZATION FOR ROBUST STABILIZATION OF GROUND VEHICLES INFORMATION-MEASURING DEVICES - Tunik, Anatoliy; Sushchenko, Olga (Proceedings of National Aviation University (archive), 2014)
The statement of the vector robust parametric optimization problem taking into consideration two groups of constraints such as the stability conditions and the requirements to performance, as well as the uncertainties of the mathematical models of the controlled plant and external disturbances is represented. It was applied to the parametric synthesis of the robust system for stabilization of the information-measuring devices at the moving base is implemented. The interactive heuristic two-step procedure for this problem solution is proposed. Efficiency of the suggested procedure is proved by the simulation results